(untitled) (Revista Brasileira de Contabilidade e Gestão, 2018)
E-commerce or e-commerce emerges as a strategic tool to help companies expand their customer network by providing better quality sales and delivering what they really need, and thereby increase the profits of organizations. The objective is to identify the strategies used to leverage the e-commerce of a home textile industry of Brusque. To support the study, the theoretical foundation presented the following themes: E-commerce, E-commerce in Brazil and Digital Marketing. Through bibliographic research and interviews, we verified that the main strategies used by the company were: adjust prices, obtain product quality, create an environment to facilitate navigation, develop financial advantages to the customer (free shipping, discount coupons), participation in marketplaces, create social networks like Instagram and Facebook, post in social media daily, to increase contact with the client. In addition, it was found that the support of a specialized service can positively contribute to leverage sales of an e-commerce website, since the implemented actions resulted in increased sales and profit. After following these steps, we find that the company has a greater number of visitors and buyers in their website.